Proactive, Reactive, and Aggressive Offending of Middle School Students: The Mediating Role of School Climate and Self-Control - Sarah Jawad Kadhim, Arkan Bahlol Naji, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Violence in schools represents an issue that continues to capture a large measure of public interest. Incidents of interpersonal violence that range from chronic verbal threats to death continue to occur at school when classes are in session; a setting widely regarded as an enclave of safety and security. Objective(s): The aim of this study is to determine proactive, reactive, and aggressive offending of middle school students: the mediating role of school climate and self-control. Methodology: The descriptive correlational design has been considered a subtype of correlational research, with its primary purpose being to examine relationships between and among variables and it is referred to occasionally as simple correlational design. (Gray et al., 2017). The study was carried out at public middle schools for males and females in Baghdad City. The study included a convenience sample of male and females middle school students who agreed to participate in this study. The study subjects were recruited from six public middle schools. Thus, the recommended sample size would be 305. Results: There is no statistically significant difference in proactive, reactive, and aggressive offending among gender groups. Conclusion: Students in all grades are invariants in terms of their practicing of proactive, reactive aggressive offending. The that the greater the willingness to seeking help, the larger the prevalence of bullying. Recommendations: There is a need for the community health nurses to establish school-based anti-violence health campaigns.